Geomorphological and environmental changes in Western Greece: a remote sensing perspective - Vassilakis, E.; Verykiou-Papaspyridakou, E. (Bulletin of the Geological Society of Greece, 2011)
Several rapid geomorphological changes can be detected on the landscape of western Greece since the area is adjacent to the highly active Hellenic trench, where major geodynamic phenomena occur. At this part of the Hellenides, various active structures have been affecting the shallow layers of the overriding plate, due to tectonic movements and in some cases gypsum diapirism. Additionally, lots of environmental implications have been reported since a significant amount of development infrastructure is still being constructed in this area for more than the last twenty years, affecting the slower physical ongoing processes. The outcropping erodible lithologies of flysch in conjunction with the existence of high energy rivers reveal a rapidly evolving area with dynamic topography, which can be identified by using the appropriate methodologies. Remote sensing techniques prove to be the ideal way to locate changes at the physical geography of the studied area, especially when multi-temporal interpretation is implemented. In this paper we try to locate and analyze these changes by using medium resolution satellite images (Landsat TM and ETM+) of different temporal periods (1992, 2000 and 2005). After special interpretation of the acquired remote sensing images, which involves detailed co-registration and spectral analysis, the identified changes can be temporally cate-gorized between the three acquisition dates. The methodology requires the compilation of new sepa-rate datasets, one for each spectral channel from the three Landsat images, in order to detect chang-es in the absorption and reflection spectra for specific bandwidths. The results show that many parts of the river valleys and the main land surface seem to have been violently altered in several parts and also significant coastal changes have been detected along the deltaic fans of Evinos and Mornos rivers, during the 13-year observation period between 1992 and 2005.